Nimrod: a tool for performing parametised simulations using distributed workstations - Abramson, D; Sosic, R; Giddy, J; Hall, B (Proceedings of the IEEE International Symposium on High Performance Distributed Computing, 1995)
This paper discusses Nimrod, a tool for performing parametised simulations over networks of loosely coupled workstations. Using Nimrod the user interactively generates a parametised experiment. Nimrod then controls the distribution of jobs to machines and the collection of results. A simple graphical user interface which is built for each application allows the user to view the simulation in terms of their problem domain. The current version of Nimrod is implemented above OSF DCE and runs on DEC Alpha and IBM RS6000 workstations (including a 22 node SP2). Two different case studies are discussed as an illustration of the utility of the system.